2007
DOI: 10.1016/j.carres.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of reference standards to enable single cell metabolomic studies of tetramethylrhodamine-labeled ganglioside GM1

Abstract: Ganglioside GM1 and its seven potential catabolic products: asialo-GM1, GM2, asialo-GM2, GM3, Lac-Cer, Glc-Cer and Cer, were labelled with tetramethylrhodamine (TMR) to permit ultra-sensitive analysis using laser-induced fluorescence (LIF) detection. The preparation involved acylation of the homogenous C18 lyso-forms of GM1, Lac-Cer, Glc-Cer and Cer with the N-hydroxysuccinimide ester of a β-alanine-tethered 6-TMR derivative, followed by conversion of these labelled products using galactosidase, sialidase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…After 12 h of reaction time, 75 mg of pure lyso-GM1 was isolated using Sep-Pak tC18 cartridges (90% yield). The yield was much larger than has previously reported for the aqueous-organic biphasic system (62-72% yield with 2 weeks of reaction time) ( 22,36 ). In addition of 100 mM Ca 2+ enhanced the yield to 81.6% ( Fig.…”
Section: Application To Large-scale Preparation Of Lyso-gm1mentioning
confidence: 58%
See 3 more Smart Citations
“…After 12 h of reaction time, 75 mg of pure lyso-GM1 was isolated using Sep-Pak tC18 cartridges (90% yield). The yield was much larger than has previously reported for the aqueous-organic biphasic system (62-72% yield with 2 weeks of reaction time) ( 22,36 ). In addition of 100 mM Ca 2+ enhanced the yield to 81.6% ( Fig.…”
Section: Application To Large-scale Preparation Of Lyso-gm1mentioning
confidence: 58%
“…These limitations make the aqueous-organic biphasic system ineffi cient for the preparation of lyso-GSLs, especially on a larger scale. As two examples, lyso-GM1 was prepared at the 10 to 20 mg scale using the biphasic system ( 22,36 ). After 2 weeks of reaction, the yield of lyso-GM1 was 62-72% ( 22,36 ), which is similar that produced by chemical catalysis ( 19 ).…”
Section: +mentioning
confidence: 74%
See 2 more Smart Citations
“…The usefulness of BODIPY in lipid and glycolipid metabolism studies was first demonstrated in a set of studies by Pagano et al (22,23) where cellular uptake was observed. To facilitate the preparation of various fluorescent GSLs without protecting group manipulation on the sugar moiety, we utilized readily available glycolipids and modified them with commercial or recombinant enzymes (24,25).…”
Section: B-1 Chemo-enzymatic Syntheses Of Fluorescentlylabeled Gsl Amentioning
confidence: 99%